2012
DOI: 10.1002/ejic.201200662
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Amino Acids into Eu3+‐Doped Layered Gadolinium Hydroxide and Quenching of Eu3+ Luminescence

Abstract: The NO3–‐type Eu3+‐doped layered gadolinium hydroxide (NO3–LGdH:Eu) was prepared by a developed homogeneous precipitation method through hexamethylenetetramine (HMT) hydrolysis with hydrothermal treatment. Two amino acid anions, phenylalanine (Phe) and tyrosine (Tyr), were intercalated into LGdH:Eu to form composites Phe–LGdH:Eu and Tyr–LGdH:Eu. Photoluminescence studies show that the incorporation of Phe and Tyr into the host layer can sharply quench the Eu3+ luminescence. This simple method is expected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…It is noteworthy that the intercalation of amino acid anions, especially Tyr, into LEuH largely weakened the emission intensity of Eu 3+ , which was also found in our previous work 11. The luminescence quenching effect of this kind of organic compounds may be ascribed to the significant nonradiative relaxation channels provided by the high‐energy vibration of the –NH 2 group, as the –OH group previously reported 20.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the intercalation of amino acid anions, especially Tyr, into LEuH largely weakened the emission intensity of Eu 3+ , which was also found in our previous work 11. The luminescence quenching effect of this kind of organic compounds may be ascribed to the significant nonradiative relaxation channels provided by the high‐energy vibration of the –NH 2 group, as the –OH group previously reported 20.…”
Section: Resultsmentioning
confidence: 99%
“…We have also investigated the enhancing/quenching effect of different organic anions such as 2,2'-biphenyldicarboxylic acid, 1,3,5-benzenetricarboxylic acid, quinolinic acid, 2,5-pyridinedicarboxylic acid, phenlylalanine, and tyrosine [21]. The doped LRH layers (with more than two RE ions in the layers) such as LYH:Eu [22,23] and LGdH:Eu [24,25] were also prepared and luminescence property of Eu 3+ intercalated by certain organic guests were studied. Tang et al reported the enhanced luminescence of layer Tb 3+ induced by synergistic effect of Gd 3+ and organic sensitizers [26], and they utilized the salicylic acid to sensitize LGdH:Tb 0.5-x Eu x fluorescence [27].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to LRH/organic composites, most of the investigations focused on Eu-involving LRHs, for example our recent work for LEuH, LYH:Eu and LGdH:Eu, in which enhancement or quenching for Eu 3+ luminescence by the introduced organics was found. [29][30][31][32] Studies on layered terbium hydroxide (LTbH) composites with organic compounds are relatively rare, 33,34 and they mainly involve the luminescence of the layer Tb 3+ rather than interlayer organics.…”
Section: Introductionmentioning
confidence: 99%